AB1052 Comparison of several biomarkers (MMP-2, MMP-9 AND ITS INHIBITOR TIMP-1, CTX-II, CALPROTECTIN AND COMP) in the synovial fluid and serum of patients with and without septic arthritis. (12th June 2018) - Couderc, M.; Peyrode, C.; Pereira, B.; Miot-Noirault, E.; Mathieu, S.; Soubrier, M.; Dubost, J.-J.
Abstract : Background: Diagnosing septic arthritis (SA) is an emergency, and for a diagnosis to be made a microorganism must be found in the synovial fluid or blood culture. Besides direct bacteriological examination, which is positive in only 25% to 50% of cases, no laboratory examination can differentiate SA from other forms of arthritis. Objectives: To assessed the performances of several serum and synovial biomarkers (matrix metalloproetinase [MMP]−2, MMP-9, the metalloproteinase inhibitor [TIMP]−1, cartilage oligomeric matrix protein [COMP], C-terminal telopeptide of type II collagen [CTX-II], and calprotectin [CALP]) for discriminating between septic and non-SA in a population of patients with suspected SA. Methods: Using the ELISA technique, a number of potential biomarkers (MMP-2, MMP-9, TIMP-1, COMP, CTX-II, and CALP) were measured in the synovial fluid and serum of 39 patients with suspected SA (of whom 21 had SA and 18 non-SA). (. The levels of the various markers were compared on univariate and then multivariate analysis using logistic regression. Results: The two groups were similar in terms of age, gender, history of diabetes and type of joint affected. SA patients had higher whole blood white blood cell counts (p=0.03) but similar C-reactive protein levels. Synovial fluid was more frequently turbid in septic cases than in non-septic ones. Serum TIMP-1 (p=0.003), synovial MMP-9 (p=0.002), serum (p=0.03) and synovial CTX-II (p=0.004), and serum (p=0.04) and synovial CALP (p=0.03) were significantly higher in the septic group than in the non-septic group. The AUCs for diagnosing SA of synovial MMP-9, serum TIMP-1, synovial CTX-II, and serum and synovial CALP were, respectively, 0.84, 0.79, 0.81, 0.7 and 0.72. A combination of serum TIMP-1 and synovial CTX-II led to 75% sensitivity and 94% specificity for diagnosing SA (AUC 0.89) and correctly classified patients in 86% of cases. Serum TIMP-1 and synovial CTX-II did not correlate with each other (r=0.1) and did not correlate with C-reactive protein (r=0.4 and r=0.25, respectively) or synovial white blood count (r=−0.04 and r=0.27, respectively). Conclusions: The combination of two laboratory measurements, serum TIMP-1 and synovial CTX-II, may make it possible to differentiate SA from other forms of arthritis in 86% of cases. These results need to be confirmed in larger samples of patients. Disclosure of Interest: None declared